The Influence of Price, Promotion and Product Quality on Affinois Purchase Decisions - Ferdinand Ferdinand; Ella Silvana Ginting; Nasrul Effendi (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to analyze the effect of price, promotion and product quality on Affinois purchasing decisions partially or simultaneously. The sampling technique was using probability sampling technique with a proportionate stratified random sampling approach, the number of samples in this study amounted to 95 respondents. The method of data analysis used multiple linear regression analysis. Based on the research, it was found that the price and promotion variables partially influence the purchasing decision, while the product quality variable partially has no effect on the purchasing decision. However, simultaneously variables, price, promotion, and product quality affect purchasing decisions. The result of the coefficient of determination is 50.2%, this shows that the variables consisting of price, promotion and product quality affect the purchasing decision variables by 50.2%. While the remaining 49.8% is explained by other variables not examined in this study.